2007
DOI: 10.1007/s00436-007-0550-7
|View full text |Cite
|
Sign up to set email alerts
|

Spermiogenesis and sperm ultrastructure of Deropristis Inflata Molin, 1859 (Digenea, Deropristidae), a parasite of Anguilla anguilla

Abstract: To our knowledge, this paper describes the first ultrastructural results on spermiogenesis and the spermatozoon of a Digenea belonging to the family Deropristidae, Deropristis inflata. Spermiogenesis follows the usual pattern found in the digeneans, but a single noteworthy characteristic concerns the centriole, which presents a "prominent pear-shaped electron-dense region." Spermiogenesis in D. inflata begins with the formation of a differentiation zone. The two centrioles give rise to flagella. These two flag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 42 publications
4
36
0
Order By: Relevance
“…The two most external layers are discontinuous. It is the case in Deropristis inflata (Foata et al 2007). The absence of striated roots and intercentriolar body was mentioned only in Didymozoide Gonapodasmius by Justine and Mattei (1982a, b) who reported that this absence does not affect the phenomena described by Burton (1972).…”
Section: Discussionmentioning
confidence: 99%
“…The two most external layers are discontinuous. It is the case in Deropristis inflata (Foata et al 2007). The absence of striated roots and intercentriolar body was mentioned only in Didymozoide Gonapodasmius by Justine and Mattei (1982a, b) who reported that this absence does not affect the phenomena described by Burton (1972).…”
Section: Discussionmentioning
confidence: 99%
“…The two most external layers are discontinuous. It is the case in Deropristis inflata (Foata et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is the case in Neochasmus sp. , Maritrema linguilla (Hendow and James 1988), Paragonimus ohirai (Orido 1988), Fasciola hepatica (Stitt and Fairweather 1990), Postorchigenes gymnesicus (Gracenea et al 1997), Notocotylus neyrai (Ndiaye et al 2003b), Monorchis parvus (Levron et al 2004a), Poracanthium furcatum (Levron et al 2004b), Dicrocoelium hospes (Agostini et al 2005), Troglotrema acutum (Miquel et al 2006), Deropristis inflata (Foata et al 2007), and Crepidostomum metoecus (Quilichini et al 2007a). The spermatozoon of Sandonia sudanensis contains three mitochondria (Ashour et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, seven electron-dense layers were described in the paramphistomoids Paramphistomum microbothrium, Cotylophoron cotylophorum, Carmyerius endopapillatus, Basidiodiscus ectorchus, Sandonia sudanensis and D. subclavatus (Ashour et al 2007;Seck et al 2007Seck et al , 2008aBakhoum et al 2011a), the allocreadiid C. metoecus (Quilichini et al 2007b), or the opecoelids Opecoeloides furcatus (Miquel et al 2000), and Poracanthium furcatum (Levron et al 2004b). Intercentriolar bodies composed of nine electron-dense layers are described in Cryptocotyle lingua (Rees 1979) and M. parvus (Levron et al 2004a) and others composed of six layers in Deropristis inflata by Foata et al (2007). In W. capitellata the intercentriolar body is composed of six electron-dense layers.…”
Section: Spermiogenesismentioning
confidence: 99%